Pengembangan Multimedia Interaktif Biologi Kelas XI Untuk Meningkatkan Motivasi dan Kemandirian Belajar Peserta Didik - Nani Kurnia; Adnan Adnan; Akhmad Faqih Dzulkarnain (Seminar Nasional LP2M UNM, 2019)
Education plays an important role to ensure the survival of a nation and state, and to develop the quality of human resources. The success of the learning process is determined by many aspects one of which is the quality of learning media used in the classroom. One solution that can be done by teachers to teach students by participating and utilizing technology that has developed. The era of the industrial revolution 4.0 or the fourth world industrial revolution where information technology has become the basis in human life. Preparing graduates who are qualified and able to compete globally, and mastering technological development is important for everyone and important for the future of a country. The use of electronic learning media can build knowledge and increase student learning interest. Research shows that giving and involving students in doing academic tasks can build initial knowledge and understanding of students which tends to increase student motivation and understanding so that the nature of learning shifts from teacher centered to student centered. Cell material and developmental growth were chosen because they have abstract material content so that researchers develop interactive biology based on Mindjet Mindmanager biology that makes it easy for students to understand the material and provide varied learning. Mindjet Mindmanager is one program that supports information technology-based learning with the aim of facilitating teachers and students and shaping innovation and computer-based learning creations. This study aims to develop interactive biology based on mindjet mindmanager on cell matter and growth and development that are valid. This developmental research was carried out by adopting the ADDIE development model. The resulting product is in the form of interactive biology multimedia. The results showed that interactive biology based on mindjet mindmanager is valid and suitable for use by teachers and students.